Handbook of Wind Power Systems - Pardalos, Panos M.; Rebennack, Steffen; Pereira, Mario V. F.; Iliadis, Niko A.; Pappu, Vijay; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Wind power is currently considered as the fastest growing energy resource in the world. Technological advances and government subsidies have contributed in the rapid rise of Wind power systems. The Handbook on Wind Power Systems provides an overview on several aspects of wind power systems and is divided into four sections: optimization problems in wind power generation, grid integration of wind power systems, modeling, control and maintenance of wind facilities, and innovative wind energy generation. The chapters are contributed by experts working on different aspects of wind energy generation and conversion.
Part 1: Optimization in Wind Power Generation -- Part 2: Grid Integration of Wind Power Systems -- Part 3: Modeling, Control and Maintenance of Wind Facilities -- Part 4: Innovative Wind Energy Generation.
Keywords: Science (General).; Electric engineering; Renewable energy sources; Energy; Renewable and Green Energy; Energy Systems; Energy Technology; Science, general